Recent Progress of Development of Optogenetic Implantable Neural Probes - Zhao, Hubin (International journal of molecular sciences, 2017)
As a cell type-specific neuromodulation method, optogenetic technique holds remarkable potential for the realisation of advanced neuroprostheses. By genetically expressing light-sensitive proteins such as channelrhodopsin-2 (ChR2) in cell membranes, targeted neurons could be controlled by light. This new neuromodulation technique could then be applied into extensive brain networks and be utilised to provide effective therapies for neurological disorders. However, the development of novel optogenetic implants is still a key challenge in the field. The major requirements include small device dimensions, suitable spatial resolution, high safety, and strong controllability. In this paper, I present a concise review of the significant progress that has been made towards achieving a miniaturised, multifunctional, intelligent optogenetic implant. I identify the key limitations of current technologies and discuss the possible opportunities for future development.